THE EFFECTIVENESS OF METRONIDAZOLE GELS IN THE MANAGEMENT OF PERIODONTAL DISEASE - Citra Jasmin Cangara; Hasanuddin Thahir (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction : Metronidazole is one of the antimicrobial and antimicrobial that has been  widely used as antibacterial and antiprotozoal agent for treatment. Metronidazole is antimicrobial have been used as an adjuvant to mechanical plaque removal. Periodontal disease is a chronic inflammatory disease that develops from dental plaque that affects periodontal supporting tissues. Many chemical agents that have been evaluated to determine their effect on plaque, gingivitis and periodontitis, one of which is metronidazole, has been successfully introduced and studied extensively. This literature review explains effectiveness of metronidazole gels in the management of periodontal disease. Review : Metronidazole (MTZ) is frequently used in the treatment for periodontal diseases since it can be against several Gram-negative anaerobic rods, the pathogenesis of periodontitis. It can be administered via oral and topical routes. However, the systemic adverse effects may in the oral cavity if used peroral. Hence, topical administration is preferable. The bacterial reservoirs not eliminated by conventional periodontal therapy can be further suppressed with the use of chemotherapeutic agents. Localized antimicrobial therapy, in particular, has evoked growing interest because of the site‑specific nature of periodontal infections, the higher concentration of anti‑microbial agent subgingivally and reduced side‑effects of systemic antibiotic use. Among the various locally delivered chemotherapeutic agents metronidazole, a has bactericidal action against anaerobes, such as Prevotela intermedia, Porphyromonas gingivalis, Tannerella forsythia, Fusobacterium species and spirochetes like Treponema denticola, Treponema vincentii, which are generally believed to be the main pathogens associated with periodontitis. Conclusion : Treatment of periodontal pockets with metronidazole gel in addition to scaling and root planning, provides a significant increase in reducing pocket depth and microbial count and effective in the treatment of periodontal disease.